Simulasi Perbandingan Motor Listrik dengan Mesin Pembakaran Dalam Sebagai Penggerak Sepeda Motor CVT - Abdussalam, Muhammad Zayyana; Arini, Nu Rhahida; Windarko, Novie Ayub (The Indonesian Journal of Computer Science, 2025)
Fuel vehicle conversion to electric vehicle requires electric motor with power equivalently to the vehicle’s fuel engine. Some CVT motorcycle conversion experiment using BLDC motor propulsion resulting 40 km/hour maximum velocity electric vehicle. This study uses computer simulations to compare the performance of electric motor and gasoline fueled internal combustion engine. The results show that fuel vehicle performance overthrow electric vehicle where 200 kg total vehicle mass absorbing power about 4,9 kW for fuel vehicle and 2,8 kW for electric vehicle then 63 km/hour maximum velocity for fuel vehicle and 53 km/hour for electric vehicle. Those result become equal when both propulsion have equal input where absorbed power reach 2,7 kW and maximum velocity reach 50 km/hour.